KEPUASAN PELANGGAN TERHADAP MODERN COFFEE SHOP: ANALISIS KUALITAS PELAYANAN FORE COFFEE DENGAN MODEL SERVQUAL - Wafa Zabitha Jhonaidi; Husna Leila Yusran; Awal Ferdiansyah; Deva Sasqi Khairunnisa (Politeknik Negeri Lhokseumawe, 2026)
Using a service quality approach, consisting of five dimensions: tangibles, reliability, responsiveness, assurance, and empathy, this study investigates how Fore Coffee's service quality impacts the company's customer satisfaction. With 141 people completing an online questionnaire, a quantitative method was applied. The results of validity and reliability tests indicate that the indicators used are valid and reliable. With a p-value of 0.000, service quality has a significant effect on customer satisfaction, according to the regression analysis. The determination test shows that service quality explains 43.3% of customer satisfaction. Improvements in responsiveness and empathy are needed to increase customer satisfaction. This study provides recommendations for increasing service speed and customer care to strengthen Fore Coffee's competitiveness.Keywords: service quality, customer satisfaction, service quality, Fore Coffee, regression.